(3eUGOQ GdeYdheGJ aj GdCHMGK GdJQHhjI GdYQHjIs - (3LYLY, gfGOjs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3cdjI GdGYdGes, 2014)
(3jgOa gPG GdHMK Edi EdbGA GdVhA Ydi HYV NUGFU eUGOQ GdeYdheGJ GdJj jSJYedgG GdHGMK GdJQHhj GdYQHj dcJGHI CHMGKg aj GdOhQjGJ GdJQHhjI GdYQHjI GdeMceI, eKd fhY GdeUOQ, YeQg, dZJg, GdN(B. (3ef CLd eYQaI ecGfI GdHGMK GdYQHj ef GdGJUGd GdYdej GdYGdej(B. (3ceG Cdbj GdVhA Ydi Gdejhd GdLZQGaj ddHGMK ef NdGd GdHdOGf GdJj GSJYed efgG GdYOO GdCcHQ ef eUGOQg, hCdbj GdVhA CjVkG Ydi fSHI GdeUGOQ GdEdcJQhfjI(B. (3afhYjI eUGOQ GdeYdheGJ JHqjf ef LgI fhYjI GdCHMGK GdJQHhjI GdJj JUOQ aj GdHdOGf GdYQHjI GdeTehdI aj gPg GdOQGSI, hef LgI CNQi eOi EbHGd GdHGMKjf Ydi GdGfNQGW HJbfjGJ GdGJUGd GdYdej GdYGdej(B. (3ddJhqUd dCQbGe JLjH Yf CSFdI GdOQGSI GJNPJ GdOQGSI GdefgL GdhUaj eSJYedkI COGI GdHjHdjheJQjI aj JMdjd GdGSJTgGOGJ GdeQLYjI(B. (3JCqdaJ YjfI GdHMK ef eFI ebGd HGddZI GdYQHjI UGOQI GdYGe (B2013 (3aj OhQjGJ JQHhjI eMqceI(B. (3Jqe JhRjY GdYjfI Ydi (B25 (3ebGd aj cqd ef eUQ, GdchjJ, GdCQOf hGdHMQjf(B. (3HdZ eLehY GdGSJTgGOGJ ajgG (B3,636 (3GSJTgGOG(B: 802 (3aj eUQ, (B868 (3aj GdHMQjf, (B843 (3aj GdCQOf h(B1123 (3aj GdchjJ(B. (3JhqUdJ GdOQGSI Edi YOO ef GdfJGFL CgqegG Cf GdHGMK GdJQHhj GdYQHj jejd Edi GSJNOGe eUGOQ hQbjI, Cqf GddZI GdEfLdjRjI cGfJ GdCcKQ GSJYeGdkG Hjf GddZGJ, ceG Cqf JGQjN GdeUGOQ cGf bOjekG fSHkI Edi JGQjN fTQge(B. (3CqeG aj eG jNU GdeUGOQ GdEdcJQhfjI, GdeUGOQ GdCLfHjI hGdeUGOQ GdMOjKI abO cGfJ GdCbqd GSJNOGekG(B. (3HGdfSHI dfhYjI GdeUGOQ, JUqOQJ GdebGdGJ hGdcJH, ajeG cGfJ GdQSGFd GdLGeYjI hGdJbGQjQ hChQGb GdeDJeQGJ Cbqd GSJNOGekG HcKjQ(B. (3ceG NdUJ GdOQGSI Edi Cf GdeUGOQ GdYGdejI eSJYedI CcKQ ef GdeUGOQ GdEbdjejI, hJdjgG GdeUGOQ GdeMdjI(B. (3JfqhYJ GdfJGFL Hjf GdHdOGf GdCQHYI, hbO CXgQJ GdfJGFL GfYcGS GdhVY GdGbJUGOj ddHdO hGdeDSSGJ Ydi eUGOQ GdeYdheGJ GdeSJYedI ef bHd GdHGMKjf(B. (3Jqe GdGSJfJGL Cf GdHGMK GdJQHhj GdYQHj eG RGd HYjO Yf hSGFd GdGJUGd GdMOjKI hZjQ efOeL HbfhGJ GdGJUGd ZjQ GdQSej GdJj JTqcd CMO Cgqe YfGUQ GdGfJGL GdYdej GdMGdjs
(3GdfhY (B: (3QSGdIs
Keywords: Educational Research; Recherche en Education; (3GdHMK GdJQHhjs